Wong Yoke Bing receives the Academic Excellence Prize of the President of the Board of Engineers Malaysia (BEM) - Norhidayah, Mohamad (2022)
PAYA BESAR, 6 November 2022 – Universiti Malaysia Pahang (UMP) graduand Wong Yoke Bing received the Presidential Award of Academic Excellence from the Board of Engineers Malaysia (BEM) at the UMP 17th Convocation Ceremony held at the UMP Sports Complex Hall.